Photoluminescence and gas sensing study of nanostructured pure and Sn doped ZnO - Navale, Shalaka C.; Mulla, Imtiaz S. (Materials Science & Engineering C-Biomimetic and Supramolecular Systems, 2009)
The nanostructured pure and Sn doped ZnO have been synthesized by the thermal evaporation technique. The influence of Sri oil the morphology and structure is investigated by using scanning electron microscopy (SEM), X-ray diffraction (XRD) and energy dispersive X-ray (EDX) analysis techniques, The SEM images indicate change in the growth pattern from nanowires of pure ZnO to tetrapods for Sn doped ZnO. Pure ZnO nanowires exhibit selective response towards acetone vapors while on Sri doping the response decreases. The non-stiochiometry and the morphology of ZnO arc probably responsible for such a difference in gas response. However increase in temperature doesn't improve the sensing behavior. The photoluminescence (PL) Studies reveal UV emission in pure ZnO which shifts to green emission oil doping of Sri. All rights reserved. (C) 2008 Elsevier B V. All rights reserved.
Keywords: Acetone; Gas sensors; Sn doped ZnO